Transmission of IMI-2 carbapenemase-producing Enterobacteriaceae from river water to human - Laurens, Chrislène; Jean-Pierre, Hélène; Licznar-Fajardo, Patricia; Hantova, Stefaniya; Godreuil, Sylvain; Martinez, Orianne; Jumas-Bilak, Estelle (Journal of Global Antimicrobial Resistance, 2018)
•Carbapenemase-producing enterobacteria transmitted from river to human.•The river carbapenem-resistant community partially replaced the human microbiota.•Surveillance of carbapenem resistance should include environmental reservoirs. Carbapenemase-producing Enterobacteriaceae (CPE) are increasing worldwide in human infections. The role of rivers as reservoirs is highlighted, but transmission from the environment to humans is not documented. A human case of bacteraemia caused by IMI-2 carbapenemase-producing Enterobacter asburiae following massive river water exposure underwent microbiological investigations with the aim of deciphering the origin and mechanism of infection. Clinical and environmental bacterial strains were compared by resistotyping and genomotyping using pulsed-field gel electrophoresis (PFGE). PFGE was also used to determine the location of the blaIMI-2 carbapenemase gene. The patient’s microbiota and river bacterial communities were compared by fingerprinting using 16S rRNA gene PCR–temporal temperature gel electrophoresis. Enterobacter asburiae causing bacteraemia carried the same plasmidic blaIMI-2 gene as E. asburiae strains detected in river water 1 month later. Clinical and river strains displayed identical PFGE profiles. Community fingerprinting showed the persistence in the patient’s microbiota of carbapenem-resistant bacteria, which were also autochthonous in the river community (E. asburiae, Aeromonas veronii and Pseudomonas fluorescens). Here we have identified for the first time the presence of an IMI-2-producing E. asburiae in a river in the South of France and suggest transmission from the river to a human probably following intestinal translocation. General insights into transmission of CPE from the environment to humans are gained from this case. Considering the rapid spread of CPE in humans, the risk of transfer from an environmental reservoir to human microbiota should be thoroughly investigated at least by implementing environmental surveillance of carbapenem resistance.